A Gift is Not Always a Gift: Heterogeneity and Long‐term Effects in a Gift Exchange Experiment. (18th December 2012) - Becker, Sascha O.; Messer, Dolores; Wolter, Stefan C.
<x xml:space="preserve">Abstract</x> We study gift exchange in a field experiment where a random subsample of participants in the Swiss Labour Force Survey received vouchers to be used in adult training. Actual voucher redemption can be traced, giving us the unique opportunity to study whether gift exchange in the form of participation in future rounds of the survey depends on the perceived usefulness of the gift. The group of voucher recipients as a whole has significantly higher response rates. There is considerable heterogeneity, however. Our results point to a long‐lasting gift exchange relationship only for the subgroup that redeemed their vouchers.